Types of Land Ownership in the Ancient AMU in the Roman Era (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Rome sought with all its efforts to acquire agricultural land by settling a large number of peasants in the fertile areas of the coasts of the ancient Arab Maghrib Countries (AMU) since the time of Julius Caesar to control the economy of ancient Morocco and direct it for the benefit of the Roman people. Especially after the deterioration of the Romanian economy on the Italian peninsula. The Romans pursued a policy of romanization of lands in ancient AMU, by issuing laws for the ownership of those lands, and those laws were in the interest of the Roman classes, which made it easier for them to own as much lands as possible, and even confiscated many of the hands of their owners, which helped in the emergence of new aristocratic classes. Emperor Augustus 27 BC - 14 AD is considered one of the strongest supporters of this principle, which encouraged the inhabitants of Rome to migrate and settle in ancient AMU. Thus, Augustus, and his successor, Tiberius Claudius 14-37 AD, distributed many lands to many new immigrants who were displaced from the Italian peninsula. The Romans established many cities near agricultural lands, and the city of Timgad, whose ruins are still the best witness to this, is one of the most famous of those Roman settlements in the ancient AMU, which prompted the Romans to expel the local population from their lands and acquire it. This prompted the population to make many revolts that exhausted the Roman armies, so defensive fortresses were established to prevent the local population and the Roman cities. In the ancient AMU, as a result of the Roman policy, there were two types of lands, one fertile, controlled by the Romans, and the other unsuitable for agriculture and left in the hands of its owners. The lands they acquired were divided into. -Lands granted to the Roman aristocracy. -Another part of the lands turned into colonies and was settled by the Romans who lost their lands and small properties in Italy. -And part became the share of the cavalry class, and it was granted to soldiers who finished their military services, and this type was known as fortified farms. -As for the last part, which is considered the least fertile, it was left in the hands of the local people, and they ought to pay taxes, while the other parts were exempt from those taxes.